2017
DOI: 10.1016/j.apsusc.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt nanoparticles for biomedical applications: Facile synthesis, physiochemical characterization, cytotoxicity behavior and biocompatibility

Abstract: Cobalt (Co) nanoparticles (NPs) were produced by a simple, one step hydrothermal method with the capping of oleic acid. Intrinsic structural, physiochemical and magnetic properties of Co NPs were investigated and demonstrated their applicability in biomedicine. X-ray diffraction, Raman spectroscopy and infrared (IR) spectroscopic studies confirm the single phase Co NPs with a high structural quality. The IR data revealed the capping of oleic acid via monodentate interaction. Small angle scattering studies sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
61
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(69 citation statements)
references
References 82 publications
(54 reference statements)
6
61
0
2
Order By: Relevance
“…They interpreted the shift of the carbonyl's IR band to be due to a bridging bidentate adsorption. Similarly, Ansari et al 35 presented an IR spectrum that demonstrated the chemisorption of the acid as a carboxylate onto the nanoparticles. However, they attributed the shift of the carbonyl band to a monodentate interaction.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…They interpreted the shift of the carbonyl's IR band to be due to a bridging bidentate adsorption. Similarly, Ansari et al 35 presented an IR spectrum that demonstrated the chemisorption of the acid as a carboxylate onto the nanoparticles. However, they attributed the shift of the carbonyl band to a monodentate interaction.…”
Section: Introductionmentioning
confidence: 94%
“…46 The whole system was placed in a cubic box of 25 Å a side and equilibrated in the NVT ensemble during 3 ps of Born-Oppenheimer molecular dynamics. A Nosé-Hoover thermostat 47 was set to 500 K, in accordance with the temperature of experiments (160-250 1C), 27,34,35 and a time step of 1 fs was used for the integration of the equations of motion. Fluctuations in temperature, potential energy, and Co-O bonds during the equilibration are shown in Fig.…”
Section: Metadynamics Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 Most of this work has been devoted to precious metal nanoparticles such as gold, 7 palladium 8 and platinum, 9 which display very high activity. Although unsupported cobalt (Co) nanoparticles (CoNPs) are of interest in several fields, 10,11 few studies have been reported concerning the potential application of CoNPs in catalysis, mostly applied in low-temperature liquid-phase reactions. [12][13][14] In fact, the thermal stability of unsupported metal nanoparticles is generally poor, their applicability being usually limited to liquid-phase reactions performed at low temperature; alternatively, they may be essentially regarded as model catalysts, whose activity is limited to short time-on-stream experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their exceptional attributes and reduced dimensions, they can be exploited in a large range of fields [1]. Cobalt oxides are important materials with a wide array of applications, such as, catalysts [2,3,4,5,6], different kind of sensors [7,2,4,5], lithium ion batteries [8,7,5], optoelectronic devices [9,10], combustion of hydrocarbons at gas purification [11], supercapacitors [12,13], Fisher-Tropsh syntheses [14] and biomedical sciences [1,7,12].…”
Section: Introductionmentioning
confidence: 99%